If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + 5c + -2 = 29 Reorder the terms: 15 + -2 + 5c = 29 Combine like terms: 15 + -2 = 13 13 + 5c = 29 Solving 13 + 5c = 29 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 5c = 29 + -13 Combine like terms: 13 + -13 = 0 0 + 5c = 29 + -13 5c = 29 + -13 Combine like terms: 29 + -13 = 16 5c = 16 Divide each side by '5'. c = 3.2 Simplifying c = 3.2
| 38+[23-(13+10)]= | | 5x+6=48-4x | | y*y=36 | | 1000x=(1000x-1x) | | 3m+g=2k | | 0.4y+0.7=0.2-0.1y | | -2k-3=19 | | 6x-5+1=-13 | | -7=-8 | | 198=90+x+5x | | 3x-([-5x]-11)=(-197) | | 5y+8=38 | | S=2(pie)rh | | 7(a+1)-3a=5+4(a-1)2 | | 2x+y=(-9) | | 66.6(6j+9)=3j+7 | | 7x=-1.60 | | -2(z+4)=-(z-5) | | 6(3n+4)=7(8n+4)+7 | | 3a+12=343 | | x-8-2(x+1)=-10 | | -2(3t-4)+4t=8t-9 | | 6(x-15)=3(14+x) | | 2(x+2)-4x=5(x-1) | | 3w-5(w-6)=2(10-w) | | 2(x+6)+(x+2)(x-2)=2x+8 | | X-90=8x | | 3x-4x=2x+25 | | -5(1-2m)-4m=23+2m | | -8x+41=-22 | | -5m+10=-10 | | 140-6x=462+10x |